World need to address something beyond than just a physical impact caused by COVID-19 pandemic: a prospective, multicentre study of psychosomatic impact due to COVID-19 disease - Dalal, Dhaval; Govindwar, Ankush; Gangwani, Gaurav; Save, Devendra; Nipane, Humeshwari; Gawali, Vijaykumar; Sanyal, Papiya; Sanyal, Aleya (International Journal Of Community Medicine And Public Health, 2021)
Background: Apart from the known physical impact COVID-19 pandemic also has had a significant psychic impact on the psychological health of the general population. Methods: The study was planned as a multi-centre cross sectional study and conducted between April 2020 and August 2020 at dedicated COVID-19 hospitals in India. Patients and accompanying relatives more than 18 years, of any gender visiting COVID hospital and willing to consent for the study were enrolled in the study. Study included three questionnaires namely, Generalized Anxiety and Depression Scale (GAD-7 Scale), questionnaire to evaluate anxiety and worry related to COVID-19 and socio demographics and COVID-19 related awareness questionnaire. Results: The patient health questionnaire (PHQ) indicated that while 25% experienced no anxiety highly significant number of 75% experienced varying degrees of psychological impact. On the GAD-7 scale 42% experienced no generalized anxiety; however, a significant remaining 58% experienced variable degree of psychological impact. While 77% people were reasonably aware about Government initiatives, however 73% were concerned about their families or themselves getting affected. Conclusions: Professional health care workers and Government agencies need to be keenly aware about the above results while devising treatment protocols and policy decisions.